Anxiety in Pregnant Women During the Covid-19 Pandemic: An Interpretative Phenomenological Analysis - Aprezo Pardodi Maba (Kuras Institute, 2023)
The prevalence of anxiety experienced by pregnant women during the Covid-19 pandemic could not be overlooked. This study aims to discover the various causes of anxiety experienced by pregnant women during the pandemic. After explaining the research objectives and obtaining informed consent, author interviewed seven pregnant women. All informant were married, majority of them were working, and all husbands of the interviewees also had permanent jobs. The data analyzed using an interpretive phenomenological approach. The study results show that four main themes cause anxiety in pregnant women amid a pandemic, namely immediate changes, health concerns, access to health services, and social isolation. This study highlights the prevalence of anxiety among pregnant women during covid-19 pandemic. It also emphasizes the importance of taking into consideration factors such as immediate changes, health concerns, access to health care, and social isolation while implementing intervention to reduce this issue. Furthermore, policymakers should prioritize these four main themes in arranging covid-19 mitigation guidelines or protocol specifically for pregnant women.